Impact of Vaccination, Prior Infection, and Therapy on Omicron Infection and Mortality. (23rd November 2022) - Wang, Xiaofeng; Zein, Joe; Ji, Xinge; Lin, Dan-Yu
Abstract: Background: Understanding immunity against Omicron infection and severe outcomes conferred by coronavirus disease 2019 (Covid -19) vaccination, prior severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, and monoclonal antibody therapy will inform intervention strategies. Methods: We considered 295 691 patients tested for SARS-CoV-2 at Cleveland Clinic between 1 October 2021 and 31 January 2022. We used logistic regression to investigate the association of vaccination and prior infection with the risk of SARS-CoV-2 infection and used Cox regression to investigate the association of vaccination, prior infection, and monoclonal antibody therapy with the risks of intensive care unit (ICU) stay and death. Results: Vaccination and prior infection were less effective against Omicron than Delta infection but provided strong protection against ICU admission and death. Boosting greatly increased vaccine effectiveness against Omicron infection and severe outcomes, although effectiveness waned rapidly over time. Monoclonal antibody therapy considerably reduced risks of ICU admission and death. The relatively low mortality of the Omicron variant was due to both reduced lethality of this variant and increased population immunity acquired from booster vaccination and previous infection. Conclusions: Booster vaccination and prior SARS-CoV-2 infection provide strong protection against ICU admission and death from Omicron infection. Monoclonal antibody therapy is also beneficial. Abstract : Using data from 295 691 patients who were tested for SARS-CoV-2 at Cleveland Clinic, we found booster vaccination and prior SARS-CoV-2 infection provide strong protection against ICU admission and death from Omicron infection and that monoclonal antibody therapy is also beneficial.